Argentina: dissemination of genetically modified cotton and its impact on the profitability of small-scale farmers in the Chaco province - Arza, Valeria (2012)
This article analyses the adoption of genetically modified cotton by small-scale farmers in the Chaco region of Argentina. It uses the socio-technical configuration of the technology as a conceptual framework, which postulates the existence of a set of factors that significantly affect the way in which technologies operate. Based on this framework, the article describes the conditions under which small-scale farmers in the Chaco region adopt gm cotton; and it identifies the differences between them and large-scale farmers, on which most of the literature focuses. Qualitative methodologies are used to analyse the breaks and continuities in productive practices affecting the profitability of small-scale farmers since the introduction of gm cotton. It is found that the productive difficulties they face have remained essentially unchanged, and, in some cases, have become more accentuated.